Implementation of Item Response Theory (IRT) Rasch Model in Psychometric Property Quality Analysis in Anger Management Scale (AMS-9) of Students - Nugraha, Dwi Yan; Nugraha, Dian; Daud, Muh; Widyastuti, Widyastuti; Ridfah, Ahmad (Universitas Negeri Semarang, 2023)
Research on anger management has been widely carried out, especially in Indonesia, so it is necessary to re-evaluate the psychometric characteristics of the anger management scale made by researchers using the Rasch model method. This study aims to analyze the psychometric characteristics of the anger management scale which is used to measure students' ability to manage anger emotions using the Rasch model approach. Respondents in this study were 103 respondents consisting of 35 men and 68 women with an age range of 15-19 years. This study shows that the discriminatory power of items ranges from 0.57 to 0.72. This study also shows that there are three items that are invalid in terms of the validity of the content of the anger management scale, and are classified as valid in terms of construct validity and rating scales which indicate that the answer choices given are understandable and can be differentiated by research respondents. This study also shows that the overall anger management scale is relatively reliable (α = 0.89). Therefore, the anger management scale has good quality psychometric properties and is in accordance with the Rasch model.